2018
DOI: 10.2169/internalmedicine.9262-17
|View full text |Cite
|
Sign up to set email alerts
|

Suffocation due to Acute Airway Edema in a Patient with Hereditary Angioedema Highlighted the Need for Urgent Improvements in Treatment Availability in Japan

Abstract: A 42-year-old Japanese man with hereditary angioedema suffered accidental trauma to his jaw in Shizuoka Prefecture, Japan, which gradually caused facial edema. Since plasma-derived human C1 inhibitor (pdh C1-INH) was unavailable, he had to be transferred to Juntendo University Hospital in Tokyo. Due to his severe edema, he suffered asphyxiation leading to cardiopulmonary arrest upon arrival. The patient was resuscitated and promptly treated with pdh C1-INH. In Japan, the self-administration of pdh C1-INH is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In Japan, HAE is estimated to affect 2500 patients, and the recognition of HAE by physicians is low. [15][16][17] Further, only 2 on-demand therapies are currently approved by the Japanese Ministry of Health, Labour and Welfare (MHLW) for the treatment of acute HAE attacks-IV plasma-derived C1-INH and SC icatibant-and only icatibant is approved for self-administration. 18,19 If the angioedema attack worsens after self-administration of icatibant, patients must visit their healthcare providers to receive plasma-derived C1-INH, and patients often live in fear that they will not arrive in time to the hospital or clinic.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, HAE is estimated to affect 2500 patients, and the recognition of HAE by physicians is low. [15][16][17] Further, only 2 on-demand therapies are currently approved by the Japanese Ministry of Health, Labour and Welfare (MHLW) for the treatment of acute HAE attacks-IV plasma-derived C1-INH and SC icatibant-and only icatibant is approved for self-administration. 18,19 If the angioedema attack worsens after self-administration of icatibant, patients must visit their healthcare providers to receive plasma-derived C1-INH, and patients often live in fear that they will not arrive in time to the hospital or clinic.…”
Section: Introductionmentioning
confidence: 99%
“…The responsible gene SERPING1 has been detected, although the severity and frequency of the disease vary even in the same family members (5). HAE-C1-INH can be life-threatening when severe edema develops in the upper respiratory tracts, and patients might undergo unnecessary abdominal surgical procedures for severe abdominal pain resulting from gastrointestinal edema without appropriate treatment for HAE-C1-INH (6)(7)(8). Additionally, it has been reported that it takes an average of 13.8 years from the onset of the initial symptoms to be diagnosed with HAE-C1-INH due to the low awareness of the disease in Japan (8).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HAE might present with one or several manifestations of the clinical triad consisting of skin swellings, abdominal pain attacks, and laryngeal oedema, described by Heinrich Quincke in 1882 [7]. The abdominal attacks can be very painful and severe mucosal swelling might potentially obstruct the upper airway causing asphyxiation [8-11]. Historically, fatality was reported in up to 40% of HAE patients without treatment [12-15].…”
Section: Introductionmentioning
confidence: 99%